Bringing up Baby [videorecording (Blu-Ray)] - Hepburn, Katharine, 1907-2003; Ruggles, Charlie, 1886-1970; Grant, Cary, 1904-1986; Fitzgerald, Barry, 1888-1961; Robson, May, 1858-1942; Catlett, Walter, 1889-1960; Feld, Fritz, 1900-1993 (The Criterion Collection, 2021)
All the earnest paleontologist wants is an intercostal clavicle to complete his brontosaurus skeleton. What he gets is an out-of-control toboggan ride with a scatterbrained heiress nuts about him (or maybe just nuts). Riding along are a dog named George, a leopard named Baby, a snooty society matron with a spare million, a caretaker on the sauce, and more.